LONG TERM OUTCOMES OF AUGMENTED TRABECULECTOMY WITH 5-FLUOROURACIL IN NIGERIA - Olawoye, OO, (J West Afr Coll Surg, 2017)
BACKGROUND: Glaucoma in sub-Saharan Africa has been described as a surgical disease because of the high cost of medical treatment, poor compliance and unavailability of medications AIM: This study reports the long-term outcomes and complication rates following trabeculectomy with 5-fluorouracil in a case series of Nigerians. DESIGN OF STUDY: This was a retrospective, observational, non-comparative case series. SETTING: University College Hospital, Ibadan, Nigeria. METHODOLOGY: Each patient had complete ophthalmic evaluation. The post-operative intraocular pressure (IOP), visual acuity outcomes and post operative complications were assessed. The World Glaucoma Association consensus on surgical outcome was used to evaluate surgical outcome. RESULTS: Of the 292 patients who presented with glaucoma during this period, a total of 47 eyes of 31 patients (10.6%) had trabeculectomy with 5-FU. The mean presenting intraocular pressure (IOP) was 31.8±12.2mmHg. At three years post-operatively, 48.5% achieved complete success without medications while 90.9% achieved success with or without medications at an IOP cut off of ≤21mmHg. At the same time point of 3 years and an IOP cut off of ≤15mmHg, 63.6% achieved success with or without medications. At a mean post-operative period of 43± 19.6 months, (range 12-86 months), mean IOP had reduced from a preoperative mean of 31.8±12.2mmHg to 15.4±4.7mmHg (P<0.001). CONCLUSION: Trabeculectomy with 5-Fluorouracil is effective in the long term in reducing IOP with minimal complications in this population of Nigerians.